Soil organic matter amount determines the behavior of iron and arsenic in paddy soil with microbial fuel cells - Gustave, Williamson; Yuan, Zhao-Feng; Sekar, Raju; Ren, Yu-Xiang; Liu, Jinjing-Yuan; Zhang, Jun; Chen, Zheng (Chemosphere (Oxford), 2019)
Arsenic (As) mobility in paddy soils is mainly controlled by iron (Fe) oxides and iron reducing bacteria (IBR). The Fe reducing bacteria are also considered to be enriched on the anode of soil microbial fuel cells (sMFC). Thus, the sMFC may have an impact on elements’ behavior, especially Fe and As, mobilization and immobilization in paddy soils. In this study, we found dissolved organic matter (DOC) abundance was a major determinate for the sMFC impact on Fe and As. In the constructed sMFCs with and without water management, distinctive behaviors of Fe and As in paddy soil were observed, which can be explained by the low or high DOC content under different water management. When the sMFC was deployed without water management, i.e. DOC was abundant, the sMFC promoted Fe and As movement into the soil porewater. The As release into the porewater was associated with the enhanced Fe reduction by the sMFC. This was ascribed to the acidification effect of sMFC anode and the increase of Fe reducing bacteria in the sMFC anode vicinity and associated bulk soil. However, when the sMFC was coupled with alternating dry-wet cycles, i.e. DOC was limited, the Fe and As concentrations in the soil porewater dramatically decreased by up to 2.3 and 1.6 fold, respectively, compared to the controls under the same water management regime. This study implies an environmental risk for the in-situ application of sMFC in organic matter rich wetlands and also points out a new mitigation strategy for As management in paddy soils. [Display omitted] •DOC abundance is a major determinate for the sMFC impact on Fe and As.•sMFC coupled with alternating dry-wet cycles can dramatically decreased the soil porewater Fe and As concentration.•The in-situ application of sMFC in organic matter rich wetlands may pose an environmental risk.•The combination of the sMFC with water management can be used as a new mitigation strategy for As management in paddy soils.